The Comparison of Failing Load of Architectural Fabrics of Weld Seams Between the Hot Air Welding and High Frequency Welding - Khaothong, Kunthakorn; Priyadumkol, Jetsadaporn; Ketsarapong, Prapapan (RMUTP Research Journal Sciences and Technology, 2022)
Architectural fabrics were continuously developed on their unique performance. Architects and Engineers designed them for the application of important buildings around the world despite the symptom that Architectural fabric sizes from manufactures are smaller than the application sizes. Recently, although the well-known method used to weld Architectural fabrics to enlarge their size is the high frequency welding, there were some application issues. To mitigate those issues, the researcher created the hot air welding to replace the high frequency welding in consideration on the failing loads of welded seams which are variable factors of the failing loads to indicate the weld strength and it is crucial for the Architectural fabric application. This research presents the comparison of failing load of weld seams between the hot air welding and high frequency welding by the test of Taguchi’s Orthogonal arrays L25 method. The test results demonstrated that Architectural fabrics welded by the hot air welding has the highest failing loads of wrap, equal to 95.38 kN/m and the highest failing loads of weft at 86.17 kN/m. Conversely, Architectural fabrics welded by the high frequency welding has the highest failing loads of wrap, equal to 101.37 kN/m and the highest failing loads of weft at 97.78 kN/m. Based on a forementioned results, there is no significant difference from both welding methods and thus concluded that the hot air welding could be used to replace the high frequency welding method.